Analisis Analisis Penerapan Sistem Kebakaran Aktif Sesuai Permen PU No 26/PRR/M/2008 di Apartemen Mediterania Garden Residence 2 Tahun 2022. - Dihartawan; Selvi Fathia Rahmah; Hardiman (Fakultas Kesehatan Masyarakat Universitas Muhammadiyah Jakarta, 2023)
Regulation of the Minister of Public Works Number 26/PRR/M/2008 concerning Technical Requirements for Fire Protection Systems in Buildings and the Environment. From 2011 to 2015, the total data on fires in Indonesia was 979. In 2018 a fire occurred in a shopping center or shopping center, causing a total of 37 people to die. The purpose of this study was to determine the application of an active fire protection system according to Minister of Public Works Regulation No. 26/PRR/M/2008 at Mediterania Garden Residence 2 Apartments in 2022. This research is qualitative-quantitative with a descriptive approach and uses a purposive sampling technique, analysis uses a checklist and deep interview. The results of research observations obtained after the analysis used the suitability assessment of the application of active fire protection systems, namely APAR 99.6% and Hydrant 99.6%. Implementation of an active fire protection system at Mediterania Garden Residence 2 Apartment according to standards in Minister of Public Works Regulation No.26/PTR/M/2008 by obtaining a hydrant score of 99.6% and for APAR obtaining a score of 99.6%. the application of APAR and Hydrant is quite good but must be improved in terms of routine checking and monitoring.